Digitalization and Employee Quality of Life: A Review - Chaudhary, Usha; Gupta, Kushi; Chaurasiya, Chandani; Mehta, Ayusha; Rauniyar, Rambha Kumari; Rajput, Sarbeshwar Kumar Singh; Mishra, Shila (Madhesh Journal of Interdisciplinary Research, 2026)
This review examines the implications of digitalization and remote work for employee quality of life (QoL), synthesizing evidence across physical, psychological, independence, social, environmental, safety and resource, and spiritual domains. A comprehensive review of multidisciplinary literature was conducted to evaluate the opportunities, challenges, and contextual factors associated with remote and hybrid work arrangements. Evidence from organizational, technological, occupational health, and well-being studies was integrated to develop a multidimensional understanding of QoL outcomes. The review indicates that digitalization and remote work can enhance autonomy, flexibility, work–life balance, and opportunities for personal and spiritual well-being. However, benefits are often offset by risks such as social isolation, blurred work–home boundaries, ergonomic challenges, cybersecurity concerns, and unequal access to digital resources. Outcomes vary according to individual, organizational, cultural, household, and technological factors, highlighting substantial heterogeneity in employee experiences. This review proposes a holistic framework linking remote work characteristics to multiple QoL domains and identifies critical research gaps, particularly in under-represented contexts such as Nepal and South Asia. The findings emphasize the need for longitudinal, context-sensitive research and evidence-based policies that promote equitable, sustainable, and employee-centered digital work environments.